Development of neuroendocrine neurons in the mammalian hypothalamus - Alvarez-Bolado, Gonzalo (Cell & tissue research, 2019)
The neuroendocrine system consists of a heterogeneous collection of (mostly) neuropeptidergic neurons found in four hypothalamic nuclei and sharing the ability to secrete neurohormones (all of them neuropeptides except dopamine) into the bloodstream. There are, however, abundant hypothalamic non-neuroendocrine neuropeptidergic neurons developing in parallel with the neuroendocrine system, so that both cannot be entirely disentangled. This heterogeneity results from the workings of a network of transcription factors many of which are already known. Olig2 and Fezf2 expressed in the progenitors, acting through mantle-expressed Otp and Sim1, Sim2 and Pou3f2 (Brn2), regulate production of magnocellular and anterior parvocellular neurons. Nkx2-1, Rax, Ascl1, Neurog3 and Dbx1 expressed in the progenitors, acting through mantle-expressed Isl1, Dlx1, Gsx1, Bsx, Hmx2/3, Ikzf1, Nr5a2 (LH-1) and Nr5a1 (SF-1) are responsible for tuberal parvocellular (arcuate nucleus) and other neuropeptidergic neurons. The existence of multiple progenitor domains whose progeny undergoes intricate tangential migrations as one source of complexity in the neuropeptidergic hypothalamus is the focus of much attention. How neurosecretory cells target axons to the medial eminence and posterior hypophysis is gradually becoming clear and exciting progress has been made on the mechanisms underlying neurovascular interface formation. While rat neuroanatomy and targeted mutations in mice have yielded fundamental knowledge about the neuroendocrine system in mammals, experiments on chick and zebrafish are providing key information about cellular and molecular mechanisms. Looking forward, data from every source will be necessary to unravel the ways in which the environment affects neuroendocrine development with consequences for adult health and disease.